Perfil dos métodos de análise mais usados na avaliação da influência da vegetação na temperatura do ar em ambientes externos no Brasil - Almeida, Marco Antonio Milazzo de (2018)
The objective of this paper is to present a profile of works about the influence of vegetation on air temperature mitigation in outdoor environments, highlighting the vegetation physical support, the analyzed climate and the respective method of analysis in Brazil in the last decades, in order to identify the most recurrent characteristics. As a methodology, this research compiled and analyzed dissertations, theses and scientific papers. It is verified that: [1] all the analyzed documents proved that the air temperature in places where the vegetation is present is colder than in environments where there is no vegetation; [2] most studies adopt field measurements as the main method of analysis; [3] further research is needed to consolidate the real contribution of vegetation to thermal comfort in all Brazilian climates, for different types of vegetation, types of support, amount of vegetation and their distribution.